2006
DOI: 10.1111/j.1445-6664.2006.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced herbicide doses in field crops: A review

Abstract: Farmers are becoming increasingly interested in more comprehensive weed management programs that reduce weed populations over time and in the use of reduced herbicide doses that lower their production costs. Research indicates that there is good potential to reduce the number of herbicide applications and utilize lower herbicide doses within competitive cropping systems. Diverse crop rotations, competitive cultivars, higher crop seed rates, reduced row spacing, specific fertilizer placement, and cover crops ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 66 publications
2
64
1
4
Order By: Relevance
“…Especially for systemic herbicides (as those tested in the present study), low growth rate of weeds could potentially have negative effects on herbicide efficacy. This fact may have implications in the reduction of herbicide rates in various weed control programs as an approach to reduce production costs, minimize the risk of crop and non-target injuries, lessen carryover concerns, and diminish potential surface and groundwater contamination (Blackshaw et al, 2006;Kudsk, 2008). However, to adopt this approach without risk of weed control failures, other weed control tactics need to be adopted before farmers will be able to use reduced herbicide rates.…”
Section: Resultsmentioning
confidence: 99%
“…Especially for systemic herbicides (as those tested in the present study), low growth rate of weeds could potentially have negative effects on herbicide efficacy. This fact may have implications in the reduction of herbicide rates in various weed control programs as an approach to reduce production costs, minimize the risk of crop and non-target injuries, lessen carryover concerns, and diminish potential surface and groundwater contamination (Blackshaw et al, 2006;Kudsk, 2008). However, to adopt this approach without risk of weed control failures, other weed control tactics need to be adopted before farmers will be able to use reduced herbicide rates.…”
Section: Resultsmentioning
confidence: 99%
“…The exploitation of competitiveness factors might favour the development of reduced herbicide use strategies for sugar beet (Paolini et al, 1999). Numerous research studies have indicated a few reasons for the potential successful use of reduced doses, including: 1) registered doses are set to ensure adequate control over a wide spectrum of weed species, weed densities, growth stages and environmental conditions, 2) maximum weed control is not always necessary for optimal crop yields, and 3) combining reduced doses of herbicides with other management practices, such as tillage or competitive crops, can markedly increase the odds of successful weed control (Blackshaw et al, 2006;Najafi et al, 2013). Several studies have demonstrated good weed control with reduced herbicide doses (Deveikyte, Seibutis, 2006;Domaradzki, 2009;Kucharski, 2009;Domaradzki, 2011;Najafi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The species C. canadensis can produce around 700,000 seeds per plant, depending on the conditions under which it is being grown (SHRESTHA et al, 2010). Therefore, increases in the weed seed bank may occur, compromising long-term profitability (DOYLE;STYPA, 2004;BLACKSHAW et al, 2006).…”
Section: Resultsmentioning
confidence: 99%